Hazard analysis and risk control in industrial building construction work: A review article - Ahmad Zainurrosidin Widya Pratama; Heri Wardana; Mulia; Din Aswan Amran Ritonga; Suardi; Achmad Jusuf Zulfikar (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Industrial building construction activities are widely regarded as high-risk operations due to the complexity of tasks and the involvement of various hazardous elements. Workers are frequently exposed to dangers such as falling from heights, being struck by moving or falling objects, electrical hazards, exposure to toxic substances, and musculoskeletal strains. These risks necessitate a systematic and comprehensive approach to hazard identification and risk control to ensure worker safety and operational continuity. This review article aims to synthesize relevant scientific literature published between 2018 and 2024 from reputable databases such as Scopus and Sinta, focusing on the identification of workplace hazards, methods of risk analysis, and implementation of effective mitigation strategies. The narrative review method was employed to gather and analyze findings from 28 selected studies that met predefined inclusion criteria. Results indicate that structured risk assessment tools—such as Hazard Identification Risk Assessment and Determining Control (HIRADC), Job Safety Analysis (JSA), and bowtie analysis—combined with the application of ISO 45001-based Occupational Health and Safety Management Systems (OHSMS), contribute significantly to minimizing accident rates. The review emphasizes the importance of integrating technical measures, administrative controls, and continuous safety training to develop a resilient and safety-oriented work culture in the industrial construction sector.